2023
DOI: 10.1021/acs.energyfuels.3c02258
|View full text |Cite
|
Sign up to set email alerts
|

Black Nanosheet-Enhanced Low-Salinity Water System for Improving Oil Recovery in a Low-Permeability Conglomerate Reservoir

Abstract: Black nanosheets (BNs) and low-salinity water (LSW) flooding are two effective methods for improving oil recovery in low-permeability or ultra-low-permeability petroleum reservoirs. The former focuses on emulsification and interfacial tension reduction, while the latter focuses on wettability alteration. Combining BN with LSW is expected to achieve dual effects in oil recovery. However, there has been no research on the combination effect of BN and LSW on conglomerate reservoirs. Therefore, this study aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…When the concentration of amphiphilic molybdenum disulfide (KH550-MoS 2 ) nanosheets was 0.005%, the interfacial tension with crude oil decreased to 2.6 mN/m, and the contact angle decreased from 131.2 to 51.7°. Zhu et al 24 proposed a composite oil displacement system of BN and low-mineralization water (LSW) based on BNs. BN-LSW can give full play to the synergistic effect of the two.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the concentration of amphiphilic molybdenum disulfide (KH550-MoS 2 ) nanosheets was 0.005%, the interfacial tension with crude oil decreased to 2.6 mN/m, and the contact angle decreased from 131.2 to 51.7°. Zhu et al 24 proposed a composite oil displacement system of BN and low-mineralization water (LSW) based on BNs. BN-LSW can give full play to the synergistic effect of the two.…”
Section: Introductionmentioning
confidence: 99%
“…BN-LSW can give full play to the synergistic effect of the two. Zhu et al , also examined the oil recovery effects of the BN-LSW composite imbibition system through imbibition in both tight sandstone and conglomerate reservoir cores, respectively. The BN-LSW composite system demonstrated excellent performance in wettability reversal and reducing interfacial tension, which contributed to its superior imbibition effect compared with individual BN and LSW systems for oil displacement.…”
Section: Introductionmentioning
confidence: 99%
“…When the concentration of octadecyl-modified black nanosheet reaches 100 mg/L, they reduce the oil–water interfacial tension from 18.47 to 0.27 mN/m by forming multilayer adsorption at the oil–water interface. Zhu et al , found that black nanosheets could also synergize with low-salinity water to reduce interfacial tension, alter core wettability, enhance emulsification properties, and improve imbibition oil recovery performance. Yao et al modified black nanosheet with different chain length modifiers to change their hydrophilic–lipophilic values, finding that the longer the carbon chain length of the modifier, the closer the nanosheets approached neutral wetness and the stronger the interfacial activity.…”
Section: Introductionmentioning
confidence: 99%